Chitin amendments eliminate the negative impacts of continuous cropping obstacles on soil properties and microbial assemblage - Fan, Yanli; Liu, Junjie; Liu, Zhuxiu; Hu, Xiaojing; Yu, Zhenhua; Li, Yansheng; Chen, Xueli; Li, Lujun; Jin, Jian; Wang, Guanghua (Frontiers in Plant Science, 2022)
Continuous cropping of soybean leads to soil environment deterioration and soil-borne disease exacerbation, which in turn limits the sustainability of agricultural production. Chitin amendments are considered a promising method for alleviating soybean continuous cropping obstacles; however, the underlying mechanisms of soil health promotion remain unclear. In this study, soil amendments with pure and crude chitin at different addition dosages were employed to treat diseased soil induced by continuous cropping of soybean for five years. Chitin amendments, especially crude chitin, remarkably enhanced soil pH and available nutrient contents (AP, AK, NO3--N) and improved soybean plant growth and soil microbial activities (FDA). Additionally, chitin application obviously enriched the relative abundances of the potential biocontrol bacteria Sphingomonas, Streptomyces, and Bacillus and the fungi Mortierella, Purpureocillium, and Metarhizium while depleted those of the potential plant pathogens Fusarium, Cylindrocarpon and Paraphoma. Moreover, chitin amendments induced looser pathogenic subnetwork structures and less pathogenic cooperation with other connected microbial taxa in the rhizosphere soils. The structural equation model (SEM) revealed that pure and crude chitin amendments promoted soybean plant growth by indirectly regulating soil pH-mediated soil microbial activities and potentially beneficial microbes, respectively. Therefore, the reduction strategies for continuous cropping obstacles by adding pure and crude chitin were distinct; pure chitin amendments showed general disease suppression, while crude chitin exhibited specific disease suppression. Overall, chitin amendments could suppress potential plant pathogens and improve soil health, thereby promoting soybean growth, which provides new prospects for cultivation practices to control soybean continuous cropping obstacles.